Study on the distribution characteristics of α-Solanine in different parts of Solanum nigrum based on infrared spectroscopy - Yan Liu; Jiankang Zhao; Minzhen Si (Results in Chemistry)
This study employs Fourier Transform Infrared Spectroscopy (FTIR) to quantitatively analyze the distribution patterns and metabolic roles of α-solanine across different organs (roots, stems, leaves, flowers, and fruits) of Solanum nigrum. By extracting absorbance values from key characteristic peaks (2923 cm‐1, 2853 cm−1, 1639 cm−1, 1152 cm−1, and 1072 cm−1) and applying a normalization ratio method for quantitative assessment, our results reveal that fruits serve as the primary accumulation site of α-solanine, followed by flowers and leaves, whereas the lowest concentrations are detected in roots and stems. Further analysis suggests that the high accumulation in fruits is likely associated with defensive functions and seed protection, while leaves and flowers function as the primary sites for α-solanine biosynthesis and signaling regulation, respectively. In contrast, roots and stems mainly facilitate transport and storage. This study highlights FTIR as a rapid, non-destructive technique for the quantitative analysis of plant secondary metabolites, demonstrating its potential in botanical research and biochemical profiling. Moreover, these findings provide valuable insights into the ecological roles of Solanaceae secondary metabolites and their potential applications in agriculture and pharmaceutical sciences.